If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -1 = -7 + 4x Reorder the terms: -1 + -2x = -7 + 4x Solving -1 + -2x = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -1 + -2x + -4x = -7 + 4x + -4x Combine like terms: -2x + -4x = -6x -1 + -6x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 -1 + -6x = -7 + 0 -1 + -6x = -7 Add '1' to each side of the equation. -1 + 1 + -6x = -7 + 1 Combine like terms: -1 + 1 = 0 0 + -6x = -7 + 1 -6x = -7 + 1 Combine like terms: -7 + 1 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| 4*3,14*x=314 | | i+5=6 | | a=a(a-21)-100 | | -12=k-18 | | y=12+b | | 4/3m=24 | | 3x^2+5+x=1 | | 15+k=20 | | -160=20x | | -5x-5/3=55/3 | | 3x-4=-5x+52 | | 4+j=9 | | 2w-12w=50 | | 10z-z=-3+4z-1-11 | | x+100=0.8x | | 3x=ab | | y=cos(10*x) | | -1+2x=-3x-46 | | -2(2x+3)+4=-4(3x+1) | | 3(4x-1)-9x=6(2-x) | | 10+t=42 | | 4/3m24 | | 4(5x-4)=24 | | 3a-5=-8(6+5n) | | 525+5g=1500 | | 3(-10-2x)=-102 | | 5a+34=2(1-7n) | | c(x)=2x+40 | | c(x)=5x+40 | | 17x-20=180+12x | | 7(m-3)-6(m+1)=-27 | | 10z=-10 |